Tinjauan Hukum terhadap Implementasi Peraturan Daerah No. 5 tahun 2017 tentang Penempatan Tenaga Kerja Lokal di Kabupaten Batubara - Amirtan Amirtan; Muhammad Hizbullah; Yeltriana Yeltriana; Ismed Batubara (Universitas Medan Area, 2026)
This study aims to analyze the implementation of the Regional Regulation of Batubara Regency Number 5 of 2017 concerning the placement of local workers, identify the obstacles encountered, and examine the efforts made to overcome them. The research employs a normative juridical method supported by an empirical approach through statutory and case study approaches. The findings indicate that the implementation of this regulation is carried out by the Department of Manpower, Industry, and Trade as the leading sector, focusing on increasing the placement of local workers in various sectors. In 2023, the agency demonstrated positive performance, with a labor force participation rate of 72.94% exceeding the target of 72.00%, achieving 101.31% of the target. However, several challenges persist, including the imbalance between the growth of the labor force and the availability of job opportunities, low workforce quality due to limited educational attainment, and low entrepreneurial motivation. Additionally, the limited number of formal sector jobs further widens the gap between labor supply and employment opportunities. Therefore, improving human resource quality and expanding job opportunities are essential to enhance the effectiveness of local workforce placement policies.